2016
DOI: 10.3390/c2020012
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Oxide Nano Composites for Chemical Sensor Applications

Abstract: Of late, graphene has occupied the attention of almost all researchers working globally in the area of materials science. Graphene nanocomposites are the latest additions to the wonder applications of graphene. One of the promising applications of the graphene-oxide nanocomposites is chemical sensing which is useful for monitoring the toxicity, inflammability, and explosive nature of chemicals. Well known binary oxides like ZnO, TiO 2 , SnO 2 , WO 3 , and CuO when combined with graphene in the form of nanocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…When a sensing material is exposed to air, adsorption of oxygen ions occurs at the sites of defects or functional groups on the sensing surface. They form chemisorbed oxygen species as per equations (1) and (2), by capturing free electrons from the matrix leading to reduced surface activity 36 .…”
Section: General Mechanism Of Chemiresistive Gas Sensingmentioning
confidence: 99%
“…When a sensing material is exposed to air, adsorption of oxygen ions occurs at the sites of defects or functional groups on the sensing surface. They form chemisorbed oxygen species as per equations (1) and (2), by capturing free electrons from the matrix leading to reduced surface activity 36 .…”
Section: General Mechanism Of Chemiresistive Gas Sensingmentioning
confidence: 99%
“…Introduction of nanoparticles in the base matrix helps in preventing agglomeration of layered materials (such as graphene), and increase the surface area by forming three dimensional networks; an essential part to improve the base matrix performance during sensing [41]. Also, it is reported that catalytic metals such as palladium normally improves the adsorption/desorption kinetics [62]. Furthermore, synergistic effect (cumulative response) due to the presence of different sensing hosts is very important from gas sensor perspectives.…”
Section: Relevance Of Materialsmentioning
confidence: 99%
“…These groups disturb the aromatic regions in the basal planes, that is why the layer of graphene oxide consist of both aromatic regions and oxidized aliphatic six-membered rings, which leads to distorted sp3-hybridized geometry and results in the insulating property of Graphene oxide. Normally Graphene oxide is a poor conductor but treatment with heat, light or chemical reduction most of graphene's properties can be restored [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%